Research on the Study of Evolution of Websites (International Journal of Engineering and Computer Science, 2017)
The purpose of this paper is to study the evolution of website. In the majority of research work the study of different version of same website has been neglected. Website performance is directly linked to user experience. User experience is that what keeps people on your website. The objective of this paper is to analyze the different versions of same website called Tech Team and find the changes in each version with respect to period of time. The Web analytics tools used in the research are GTMetrix, pingdom, Website pulse.